Fast-ion D alpha diagnostic with 3D-supporting FIDASIM in the Large Helical Device. (14th September 2020) - Fujiwara, Y.; Kamio, S.; Yamaguchi, H.; Garcia, A. V.; Stagner, L.; Nuga, H.; Seki, R.; Ogawa, K.; Isobe, M.; Yokoyama, M.; Heidbrink, W. W.; Osakabe, M.
Abstract: For understanding the physics of energetic particles, the deuterium experimental campaigns started in Large Helical Device (LHD) from March 2017. To investigate the behavior of energetic particles, a Fast-ion D Alpha (FIDA) diagnostic was installed on the LHD. In the FIDA diagnostic, the Doppler-shifted D alpha light from fast-neutrals are utilized as signals of energetic particles, where these fast-neutrals are produced by the charge exchange process between fast-ions in the plasma and actively injected neutrals by neutral beam (NB). The advantages of the FIDA diagnostic are the velocity and the spatially resolved measurement of fast-ions at the crossing point between its line of sight (LOS) and the incident line of NB. The most recent FIDASIM is enhanced to simulate signals produced in three-dimensional magnetic configurations. The new version of FIDASIM uses the fast-ion distribution function produced by GNET as input to simulate FIDA signals at LHD. In order to validate the new version of the code, measurements of radial profiles of fast-ions using the FIDA diagnostic are performed in magnetohydrodynamic (MHD)-quiescent plasmas. The measured spectra are in good agreement with the theoretical prediction by 3D-supporting FIDASIM at the center of the plasma ( R = 3.5 m∼3.7 m, reff /a99 = −0.28∼0.05) on the LHD when the line averaged electron density is ne_avg < 1.23 × 10 19 m −3 . On the other hand, the measured spectra are in disagreement with the theoretical prediction by 3D-supporting FIDASIM at even the center of the plasma when the line averaged electron density is ne_avg ≥ 1.23 × 10 19 m −3 .